STRUCTURAL CHANGES OF LITHUANIAN POSTAL SERVICES: POSSIBILITIES OF PENETRATION - Skačkauskienė, Ilona; Drejeris, Rolandas; Neverauskienė, Laima Okunevičiūtė; Zabarauskaitė, Rasa (Ekonomika, 2014)
Abstract. The authors analyse the Lithuanian postal service market which has become open for competition since 2013, after the Law Amending the Postal Law coming into force. The main objective of the article is to identify characteristics of the Lithuanian postal service market and to formulate market penetration proposals for new entrants. The main methods employed in the article are a comparative analysis of statistical data and a sociological survey. The article starts with the literature review on the topic, the identification of major postal service providers in Lithuania, and the analysis of their key performance indicators. This section is followed by a sociological survey and an analysis of customer comments found in the online Public Register of Legal Entities aimed at identifying the shortages of the Lithuanian postal service market and fomulating proposals how to improve the quality of postal services in Lithuania. Findings of the survey suggest that the concentration of efforts on service provision to legal entities, flexibility of service prices and service quality higher than that of competitors constitute the key factors for market penetration and gaining competitive advantages.Key words: postal service, market, the quality of postal and courier services, key factors for market penetration